H. Leibenstein, H. Brown, M. Perlman, E. Boserup, M. A. Adelman y G. Ohlin. "Population A Symposium" Quarterly Journal of Economics, 89 (2), mayo de 1975. 230-276 p. - Weiss-Altaner, Eric R. (Estudios Demográficos y Urbanos, 1975)
H. LEIBENSTEIN, H. BROWN, M. PERLMAN, E. BOSERUP, M. A. ADEL-MAN y G. OHLIN, "Population: A Symposium'', Quarterly Journal of Economics 89 (2), mayo de 1975.